A statherin-derived peptide promotes hydroxyapatite crystallization and in situ remineralization of artificial enamel caries. Issue 3 (5th January 2018) - Wang, Kun; Wang, Xiuqing; Li, Haoran; Zheng, Sainan; Ren, Qian; Wang, Yufei; Niu, Yumei; Li, Wei; Zhou, Xuedong; Zhang, Linglin
Abstract : A novel biomimetic peptide inspired by salivary statherin was developed and exhibited beneficial potentials in promoting remineralization of hydroxyapatite on tooth enamel surface, providing a desirable alternative restorative strategy against dental caries. Abstract : In situ remineralization of hydroxyapatite on a human tooth enamel surface induced by anti-caries bioactive components is an alternative restorative strategy against dental caries. In this study, a novel biomimetic peptide DE-11, inspired by the salivary phosphoprotein statherin, was developed, and it showed beneficial potentials for the restoration of demineralized tooth enamel in vitro . The peptide DE-11 contained the initial six-peptide sequence of N-terminus of statherin extended by a mineralization hydrophilic tail composed of consecutive acidic amino acids capable of adsorbing calcium and phosphate ions. A strong adsorption capacity of DE-11 to hydroxyapatite was confirmed through Langmuir adsorption isotherm experiment and confocal laser scanning microscopy. Then, the nucleation and crystallization of hydroxyapatite due to DE-11 was characterized by scanning and transmission electron microscopy and selected-area electron diffraction. Moreover, the ability of DE-11 to promote the remineralization of initial enamel caries lesions was further evaluated. Initial lesions were created in bovine enamel blocks, which were then exposed to the peptide solution and finally immersed in artificial saliva. After 7 days, a higher percentage of surface microhardness recovery, a lower mineral loss, a shallower lesion depth, and a higher mineral content were found on the surface of the lesion body in the DE-11 group as compared to that in the negative group using surface microhardness testing, polarized light microscopy, and transverse microradiography; this indicated that DE-11 could induce in situ remineralization of hydroxyapatite on the demineralized enamel surface. Overall, these findings suggest that DE-11 is highly promising as a restorative biomaterial for enamel remineralization in the anti-caries applications.